ACCEPTANCE TECHNOLOGY FACTORS OF MOBILE BANKING USAGE BASED ON UTAUT2 MODEL - Aryono Putranto, Ignatius (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
The aim of this research was to examine factors in UTAUT2was developed by Venkatesh et al.,(2012)(Unified Theory of Acceptance and Use of Technology2) Model which were influenced people in using mobile banking. Constructs used in this research were: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habits, behavioural intention, and use behaviour. This research based on survey research, and data were gathered using questionnaire. The questionnaires were distributed through internet link and it was responded by 199 respondents. The population in this research are every person who used mobile banking. The sample amount used the literature which was said that if the number of arrows in the model is maximum 10, the minimum amount of samplesare 91 samples.Data analysis techniques employed in this research was Partial Least Square–Structural Equation Modeling (PLS-SEM). Results from this research shows that the factors influencing use of mobile banking are habitss and behavioural intention. In other sides, factors that determine the intentions on using mobile banking are habitss and performance expectancy. Results of this research contributes to the identify the factors that should be enhanced by banks to optimize the use of mobile banking and also contributes to the banks customers to make them understand what factors influenced them most on using mobile banking. Theoretical contribution from this paper related to contribution of references about examining the factors affect use of mobile banking in Indonesia from the UTAUT2 model.